ANALISIS DAN EVALUASI PERENCANAAN KEGIATAN DAN ANGGARAN DINAS PEKERJAAN UMUM DAN PENATAAN RUANG KOTA PAREPARE PADA TAHUN 2019 - Akhsan, Akhsan; Talib, Anwar; Dahlan, Dinda Nur Fadhilah (Program Studi Ekonomi Pembangunan Fakultas Ekonomi dan Bisnis Universitas Muhammadiyah Parepare, 2022)
Improved economic conditions are inseparable from the important role of infrastructure. Development activities, rehabilitation, maintenance and operational subsidies have succeeded in improving the accessibility, capacity, quality, and range of services of various infrastructures, which in turn are able to provide support to various economic sectors such as agriculture, processing industry, trade and regional development. This research aims to find out the effectiveness of the implementation of the Activity Plan and Budget in the Office of Public Works and Spatial Planning of Parepare City in 2019. The subjects of the study are the Program and Finance Sub-Section of the Parepare City Office of Public Works and Spatial Planning, Data collection techniques bymeans of observation, interview and documentation. The data analysis techniques used are qualitative descriptive analysis and standard measures of effectiveness. The results of the study stated that the implementation of activities at the Office of Public Works and Spatial Planning of Parepare City can be said to be quite effective and very effective